Beliefs about cannabis at the time of legalization in Canada: results from a general population survey - John A. Cunningham (BMC, 2020)
Abstract Aims Cannabis became a legally available drug in Canada in October of 2018. The objective of this study was to examine beliefs about cannabis use at the time of legalization among past year cannabis users, those who had used cannabis but not in the last year, and people who had never used cannabis. Design and methods A survey of 813 participants, 18 years and over, and identified using random digit dialing methods, was made of the Canadian general population. Among other items, participants were asked a series of questions about their beliefs regarding cannabis use and recovery. Results Compared to never and ever users, participants who used cannabis in the last year regarded cannabis as less of a societal problem (mean [SD] past year use = 3.8 [2.4] versus 6.4 [2.6] and 6.0 [2.4] respectively, p = .001), than people were less likely to become addicted to cannabis if they tried it (past year use = 13.3% versus 48.3% and 25.1%, p = .001), and a larger proportion believed that recovery from cannabis without treatment was likely (past year use = 40.8% versus 14.2% and 19.3%, p = .001). All groups were equally positive of the chances of recovering from cannabis addiction with treatment (p = .72). Discussion and conclusion Beliefs about cannabis use vary substantially between those who have used the drug in the past year and those who have not. Replication of the survey at a later date is merited in order to assess the ways in which beliefs about cannabis evolve after an extended period of cannabis being available as a legal drug.